Obstetric history and its association with cardiometabolic risk factors: a case-control study among Bhil Women of Rajasthan, India - Kushwaha, Savitesh; Mishra, Jyoti; Mondal, Prakash Ranjan (Anthropological Review, 2021)
Pregnancy and childbearing are special reproductive events having an impact on women’s health and demographic trends. Reproductive health is not only linked to biological events of gestation and birth, but also are intricately linked to women`s status and their role in society. The current study focuses on the impact of bad obstetric history in the development of cardiometabolic risk factors. The present retrospective case-control study was conducted among Bhil tribal women of Rajasthan, India. A total of 287 women participated in this study which included 125 cases and 162 controls. Data on somatometric measurements, physiological measurements and lipid profile were recorded and analysed using SPSS version 25.0. The mean number of conceptions differed significantly between pregnancy in cases (5.06±1.85) and pregnancy in controls (3.19±1.56). Cases were characterised with significantly increased mean SBP (p=0.010), although the values (116.68±23.04) fell within the normal range. Bad obstetric history was found to be a risk factor for central obesity, hypertension and dyslipidemia among the Bhil women. It was also found to be relatively associated with adverse demographic/lifestyle variables which could enhance the effect of cardiometabolic risk factors. Women with bad obstetric history need special care and lifestyle variables need to be adjusted for better health outputs.